Current issues in the preservation of wild plant resources in the Tashkent Region (Uzbekistan) - Khojimatov, Olim K.; Khujanov, Alisher N.; Bussmann, Rainer W; Abdiniyazova, Gulnara J.; Khamraeva, D.T. (Ethnobotany Research and Applications, 2026)
Background: The article provides research on the biological resources of the natural medicinal flora of Tashkent region (Uzbekistan), which have started to decrease sharply in recent years due to anthropogenic factors. Methods: The assessment of the distribution ranges of medicinal plants was carried out using the route-reconnaissance method widely applied in resource surveys. Field observations were conducted across all foothill and mountain regions of the Tashkent Province. To ensure data comparability, the standard methodology for evaluating the stocks of medicinal and technical plant raw materials (Borisova 1966; Khojimatov 2021) was employed, which includes delineation of population boundaries, characterization of habitats, estimation of projective cover, and assessment of resource potential. Results: Annually harvested species of medicinal plants of the Tashkent region with a volume of more than 30 tons are such species as Crataegus turkestanica Pojark., Ephedra equisetina Bunge, Ferula tenuisecta Korovin, etc. Limited reserves, less than 1 ton are: Dactylorhiza incarnata subsp. cilicica (Klinge) H.Sund., Helichrysum maracandicum Popov ex Kirp., Tussilago farfara L. The main reasons for the ecological tragedy of the region and the reduction of the area of medicinal plants are the expansion of residential areas, the construction of industrial enterprises, cattle grazing, and the uncontrolled collection of plant raw materials, among others. In addition, the taxonomic analysis of the medicinal flora of the Tashkent region in recent decades and information on the dynamics of the decline of some medicinal plant resources in this region are presented. Conclusions: Based on the results obtained, we have given recommendations on the collection of plant raw materials and their use on an industrial scale only for the mountainous part of the Tashkent region, since the foothills and plains are largely subject to anthropogenic pressure, that is, there is active urbanization of the territories, industrial enterprises are being built and lands are being developed for agricultural purposes. Keywords: harvesting; medicinal plants; resources; Tashkent region; sustainable using, plant introduction.